Net reserves evaluation and sensitivity analysis of shale gas project under royalty & tax system in British Columbia, Canada. Issue 4 (February 2019) - Fa, Guifang; Yuan, Ruie; Lan, Jun; Zou, Qian; Li, Zhiyu
Abstract: With the declination of production and increasing of fossil-fuel demand, petroleum companies strive to maximize production by conducting more advanced drilling operations, such as extended reach, horizontal and high-pressure/high-temperature (HP-HT) drilling and multi-stage hydraulic fracturing, which are expanding globally into unconventional resources drilling. Shale gas, which constitutes for a significant percentage of the natural gas resource base and offers tremendous potential for future reserve and production growth, was becoming the increasingly important asset for petroleum companies. This paper took a shale gas project in British Columbia (Canada) as an example, combining the characteristics of the shale gas reservoirs with royalty & tax policy of this region. The research on shale gas reserve evaluation and the principles of net reserve calculation under royalty & tax contract was carried out. The four main aspects such as technique, economy, commerce and engineering, were studied to analyze the influence on net reserves from the following factors: production, declining rate, development plan, oil price, Opex(operating costs), Capex(investment) and taxes, etc. Sensibility analysis was conducted by adopting the most weighted factors, such as oil prices, production, Opex and Capex. All the effort was to put forward the corresponding suggestions on optimizing development strategy, solve the current reserves evaluation problems of shale gas, and provide reference for the shale gas assets transaction, development and perfection of reserves value evaluation.